Situational picture about the Hungarian prison system - Juhász, Zsuzsanna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abstract: The aim of this study is to illustrate some/or the main features of the Hungarian penitentiary system. Accordingly, the present paper attempts to introduce the main aspects of the institutions for the accommodation of inmates, as well as the most relevant information about the prisoners, prison conditions and the problems of the penitentiary system.